Analisis Kinerja Berdasarkan Penerapan E-Kinerja dan Disiplin Kerja Melalui Motivasi Sebagai Variabel Intervening (Studi pada ASN Kantor Camat Peusangan Kabupaten Bireuen) - Harahap, Rahmadsyah; Arief Syarifuddin, Endang; Yanna, Sri (Singkite Journal, 2025)
The purpose of the study was to analyze ASN performance from the implementation of E-Performance and work discipline, with motivation as an intervening variable. This is a case study of 76 Peusangan District Office Employees, Bireuen Regency. Using a quantitative approach and causality analysis where data was collected through a questionnaire. Data analysis techniques with path analysis using SMART-PLS software. The results of the study can be concluded that E-Performance has an effect on ASN Performance. And work discipline also has an effect on ASN performance. E-Performance and work discipline partially have an effect on motivation. Motivation has an effect on Performance. E-Performance is related to work discipline. E-Performance through motivation has an effect on performance. Also work discipline through motivation has an effect on performance. E-Performance through Work Discipline has an effect on Performance. And E-Performance, work discipline and motivation together have an effect on ASN Performance at the Peusangan District Head Office.